Smoking hot portfolios? Overtrading from self-control failure - Charline Uhr; Steffen Meyer; Andreas Hackethal (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
Psychology considers self-control failure, i.e., the inability to resist certain behaviors and impulses when seeking to achieve future goals as a major human pathology. The finance literature models and applies self-control failure to explain time-inconsistent behavior such as under-saving and nonparticipation decisions as a result of present bias due to hyperbolic discounting. However, literature does not investigate whether and to what extent self-control failure affects investment behavior among those who have positive savings and stockholdings. We fill this gap by identifying smoking as the most socially accepted example of present-biased preferences and link it to trading records. We compare trading behavior in the investment portfolio between 3,553 smokers and 10,091 nonsmokers over six years and show that the proportion and demographic characteristics of smokers are consistent with German survey data and federal statistics. Smoking as a proxy for self-control failure is associated with a higher number of trades per month, higher trading volume, and higher portfolio turnover and not explained by other biases such as overconfidence, social contagion, sensation seeking, or attention grabbing. But we find that self-control failure exacerbates these other biases. We show that self-control failure is costly because it increases the gap between the gross and net returns of smokers relative to nonsmokers.
Keywords: G41; D14; G21; G11; 330; self-control; individual investor; trading behavior